Globalization and the retreat of citizen participation in collective action: a challenge for public administration - Adres, Eitan; Zalmanovitch, Yair; Vashdi, Dana R. (2016)
Globalization challenges the ability of contemporary public administration to encourage citizen participation in collective action through behaviors such as tax compliance and contributions to public goods. The authors introduce a new individual-level approach to globalization, arguing that people vary in the extent to which they are globalized and that an individual's level of globalism (ILG) reflects attitudes and dispositions that influence the way he or she resolves the social dilemma of participation in collective action (i.e., the decision to contribute versus follow a "free-ride" strategy). Using a four-country sample, the article examines the relationship between ILG and collective action participation decisions in three behavioral experiments. Findings support the hypothesis that regardless of country-level globalization, a more globalized individual complies less willingly with tax codes, donates less to local nongovernmental organizations, and prefers to adopt a free-ride strategy in a public goods game. The consequences for public administration are discussed. - Reproduced. 11
Keywords: Public administration; Globalization; Workers participation